Pengaruh Soft Skills Instruktur dan Media Pembelajaran Terhadap Efektivitas Pembelajaran Peserta Kursus Komputer di CV Sri Komputer - Ni Made Widiari; Ida Ayu Nyoman Widia Laksmi; I Gede Bayu Wijaya (INDO PUBLISHING, 2026)
This study aimed to examine the influence of instructors' soft skills and learning media on the learning effectiveness of computer course participants at CV Sri Komputer. This study employed a quantitative approach involving 42 respondents selected from computer course participants at CV Sri Komputer. The data were analyzed using validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination tests. The results showed that: (1) instructors' soft skills had a positive and significant effect on learning effectiveness; (2) learning media had a positive and significant effect on learning effectiveness; and (3) simultaneously, instructors' soft skills and learning media had a significant effect on learning effectiveness. The coefficient of determination of 81.2% indicates that the variation in learning effectiveness could be explained by these two variables, while the remaining 18.8% was influenced by other factors outside the scope of this study.